Recent Advances in the Health Benefits of Tea - Hano, Christophe; Drouet, Samantha (IntechOpen, 2023)
Tea is one of the most popular beverages in the world, and the second most consumed after water. Based on evidence from cellular, animal, epidemiological, and clinical studies, tea consumption has been linked to several health benefits, including cancer chemoprevention, chronic inflammation, heart and liver diseases, diabetes, and neurodegenerative disorders. This book provides an up-to-date critical view of the health benefits of tea, including its phytochemistry, traditional usage, current applications, and future directions for the development of tea compounds as effective medicinal agents. It is a useful resource for academics, scientists, students, and industry professionals interested in tea, medicinal plants, and traditional medicines.